2022
DOI: 10.7150/ijbs.69652
|View full text |Cite
|
Sign up to set email alerts
|

Sublytic C5b-9 Induces CCL3/4 Production and Macrophage Accumulation in Thy-1N Rats via PKC-α/p65/IRF-8 Axis

Abstract: Mesangioproliferative glomerulonephritis (MsPGN) is a common human kidney disease. Rat Thy-1 nephritis (Thy-1N) is an animal model widely used for the study of MsPGN. Thy-1N is not only sublytic C5b-9-dependent, but also related to pro-inflammatory cytokine production and macrophage (Mφ) accumulation in rat renal tissues. In this study, we found that the expression or phosphorylation of chemokine CCL3/4, CD68 (Mφ marker), IRF-8, PKC-α and NF-κB-p65 (p65) were all up-regulated both in the renal tissues of Thy-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…According to our functional analysis, the progression of atherosclerosis related to immune infiltration is associated with the TNF and NF‐κB signalling pathways. Previous research has demonstrated that sublytic C5b‐9 triggers the production of CCL3/4 and accumulation of macrophages in Thy‐1 N rats through the PKC‐α/p65/IRF‐8 axis 28 . Building on this finding, we propose that the IRF8‐associated mechanism may play a role in the advancement of atherosclerosis following immune cell infiltration.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…According to our functional analysis, the progression of atherosclerosis related to immune infiltration is associated with the TNF and NF‐κB signalling pathways. Previous research has demonstrated that sublytic C5b‐9 triggers the production of CCL3/4 and accumulation of macrophages in Thy‐1 N rats through the PKC‐α/p65/IRF‐8 axis 28 . Building on this finding, we propose that the IRF8‐associated mechanism may play a role in the advancement of atherosclerosis following immune cell infiltration.…”
Section: Resultssupporting
confidence: 60%
“…Previous research has demonstrated that sublytic C5b-9 triggers the production of CCL3/4 and accumulation of macrophages in Thy-1 N rats through the PKC-α/p65/IRF-8 axis. 28 Building on this finding, we propose that the IRF8-associated Numerous studies have documented significant immune infiltration markers in atherosclerosis. [29][30][31] Our study used integrated bioinformatics analysis to identify the crucial gene IRF8, known for its association with immune deficiency.…”
Section: In Vitro Experiments Validated the Role Of Irf8 As An Immune...mentioning
confidence: 80%
“…It functions through the activation of the NF-κB pathway, playing a role in enhancing the strength and extent of the inflammatory response. [ 39 ] VCAM-1, a member of the immunoglobulin superfamily, is upregulated in DKD and plays a crucial role in immune responses and inflammatory reactions in DKD, garnering increasing attention in DKD research. [ 40 ] These molecules act through ligand-receptor interactions and are involved in various physiological and pathological processes, including inflammation, immune responses, blood coagulation, thrombosis formation, wound healing, tumor metastasis, and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The complement components, including C1q, (18) mannose-binding lectin (MBL), (19) CFB,(20) C3a, (21) and C5a, (22) etc., can extensively interact with macrophages to regulate their polarization and functions, and previous studies demonstrate that C5b-9induced kidney injury development is mediated by macrophage. (23,24) In the present study, we elucidate the possible mechanism of the C5b-9 complex-macrophage-RTEC axis in accelerating ADPKD pathogenesis in the chronic-onset PKD mice.…”
Section: Introductionmentioning
confidence: 96%